2021
DOI: 10.3390/pharmaceutics14010011
|View full text |Cite
|
Sign up to set email alerts
|

Klotho and Mesenchymal Stem Cells: A Review on Cell and Gene Therapy for Chronic Kidney Disease and Acute Kidney Disease

Abstract: Chronic kidney disease (CKD) and acute kidney injury (AKI) are public health problems, and their prevalence rates have increased with the aging of the population. They are associated with the presence of comorbidities, in particular diabetes mellitus and hypertension, resulting in a high financial burden for the health system. Studies have indicated Klotho as a promising therapeutic approach for these conditions. Klotho reduces inflammation, oxidative stress and fibrosis and counter-regulates the renin-angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 340 publications
(501 reference statements)
0
6
0
1
Order By: Relevance
“…Given that CKD is related to the prevalence of CHF, the repletion of Klotho production may give renal protection and, as a result, may help to decrease the prevalence of CHF ( 57 ). Dysregulation of Klotho axis leads to higher cardiovascular risk resulting in increased cardiovascular morbidity and mortality rates of CKD patients ( 58 ). In our study, renal function was found to significantly mediate the association between Klotho and CHF, which may signify Klotho playing important roles in the pathogenesis of CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Given that CKD is related to the prevalence of CHF, the repletion of Klotho production may give renal protection and, as a result, may help to decrease the prevalence of CHF ( 57 ). Dysregulation of Klotho axis leads to higher cardiovascular risk resulting in increased cardiovascular morbidity and mortality rates of CKD patients ( 58 ). In our study, renal function was found to significantly mediate the association between Klotho and CHF, which may signify Klotho playing important roles in the pathogenesis of CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Specific examples of the administration of recombinant s-Klotho or peptides were discussed before. Gene therapy has been performed with viral vectors or plasmids, and cell therapy also appears feasible ( Franco et al, 2021 ). In some cases, such as recombinant protein and gene therapies, the feasibility, potential adverse effects, accessibility, and high cost are likely to be limiting factors.…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%
“…Recombinant Klotho protein or peptides: Ali et al, 2020 ; Chen TH, et al, 2013 ; Doi et al, 2011 ; Gupta et al, 2022 ; Hu et al, 2017 ; Leon et al, 2017 ; Maltese et al, 2017 ; Mencke et al, 2017 ; Myung et al, 2022 ; Oh et al, 2018 ; Prud’homme et al, 2020 ; Rao Z, et al, 2019 ; Takenaka et al, 2018 , 2019 , 2020 ; Yang et al, 2015 ; Yuan et al, 2022 ; Zhong et al, 2020 . Gene therapy: Arbel Rubinstein et al, 2021 ; Franco et al, 2021 ; Lin & Sun, 2015a , b ; Ni et al, 2021 ; Mencke et al, 2017 ; Shin et al, 2019 ; Xiang et al, 2021 ; Zeng et al, 2019 . Traditional medicines, nutraceuticals and supplements: Dehghani et al, 2019 ; Feng and Huang, 2022 ; Hsu et al, 2014 ; Kamel et al, 2022 ; Long et al, 2018 ; Li SS, et al, 2018 ; Lim SW, et al, 2019 ; Long et al, 2018 ; Ostojic and Engeset, 2021 ; Zhang P, et al, 2016 ; Zhang XT, et al, 2020 ; Zhou et al, 2015 .…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%
“…17 Klotho protein is implicated in the endocrine regulation of mineral metabolism and the regulation of multiple signalling pathways. 18 FGF23 exerts its biological functions by activating the fibroblast growth factor receptor (FGFR) in renal tissues in a Klotho-dependent manner. 19 Through binding to Klotho and triggering downstream mitogenactivated protein kinase (MAPK) signalling, FGF23 induces oxidative stress and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…The Klotho gene, mainly expressed on kidney distal tubular epithelial cells, is able to generate unidirectional transmembrane proteins 17 . Klotho protein is implicated in the endocrine regulation of mineral metabolism and the regulation of multiple signalling pathways 18 . FGF23 exerts its biological functions by activating the fibroblast growth factor receptor (FGFR) in renal tissues in a Klotho‐dependent manner 19 .…”
Section: Introductionmentioning
confidence: 99%